PÁTIYA (ALǴÍS) ILIMIY MAShQALA SÍPATÍNDA HÁM ONÍŃ GENEZISI - Abdimuratov, L.A. (SCIENCE and SOCIETY, 2026)
The article examines the sources of the occurrence of the blessing found in the traditional songs of the Karakalpak people, the types of blessings, curses, and wishes, as well as the features of its use in Karakalpak folk epics.